Manual and Automated Measures of Superior Temporal Gyrus Asymmetry: Concordant Structural Predictors of Verbal Ability in Children - Eckert, Mark A. (2008)
The planum temporale is a region on the posterior surface of the temporal lobe that exhibits robust leftward structural asymmetry that has been linked to verbal ability in children and adults. Traditionally, structural asymmetry has been quantified with manual assessment of high resolution MRI scans. Such measures require subjective and frequently unreliable determination of highly variable anatomical boundaries. Methodological developments in automated image processing (voxel based morphometry -VBM) offer the opportunity to obtain objective and reliable measures of structural variation. This study examined the extent to which a VBM measure of gray matter asymmetry in the posterior superior temporal gyrus (pSTG) characterized the same individual variation as a manual measure of planum temporale asymmetry in 99 healthy adults and 39 typically developing children. Planum temporale asymmetry was significantly correlated with pSTG gray matter asymmetry in the samples of adults and children. As a measure of validity we examined the extent to which the VBM measure of pSTG gray matter asymmetry predicted measures of verbal ability that were associated with the manual measure of planum temporale asymmetry in the same children. The two asymmetry measures predicted the same variance in verbal ability. The automated measure of pSTG gray matter asymmetry predicted additional significant variance in verbal ability, however. In addition, a posterior STS region was also identified that significantly predicted verbal ability. These results demonstrate significant advantages of an automated voxel-based measure over a manual measure of planum temporale asymmetry.